2021
DOI: 10.1101/2021.11.03.21265803
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebello-thalamic activity drives an abnormal motor network into dystonic tremor

Abstract: Dystonic tremor syndromes are highly burdensome and treatment is often inadequate. This is partly due to poor understanding of the underlying pathophysiology. Several lines of research suggest involvement of the cerebello-thalamo-cortical circuit and the basal ganglia in dystonic tremor syndromes, but their role is unclear. Here we aimed to investigate the contribution of the cerebello-thalamo-cortical circuit and the basal ganglia to the pathophysiology of dystonic tremor syndrome, by directly linking tremor … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
0
0
Order By: Relevance
“…Furthermore, the abnormal cerebello-thalamo-striatal connection has been reported in patients with dystonia via diffusion tensor imaging, functional magnetic resonance imaging, and positron emission tomography (Lehéricy et al, 2013;Reeber et al, 2013;Nieuwhof et al, 2022). Recently, it has been reported that DBS of the cerebellum alleviates dystonia (Coenen et al, 2011;França et al, 2018;Horisawa et al, 2018Horisawa et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the abnormal cerebello-thalamo-striatal connection has been reported in patients with dystonia via diffusion tensor imaging, functional magnetic resonance imaging, and positron emission tomography (Lehéricy et al, 2013;Reeber et al, 2013;Nieuwhof et al, 2022). Recently, it has been reported that DBS of the cerebellum alleviates dystonia (Coenen et al, 2011;França et al, 2018;Horisawa et al, 2018Horisawa et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%